Postpartum care needs assessment: women’s understanding of postpartum care, practices, barriers, and educational needs - Yenupini Joyce Adams; Michelle Louise Miller; John Stephen Agbenyo; Ethel Emefa Ehla; Grace Anne Clinton (BMC Pregnancy and Childbirth, 2023)
Abstract Background Complications in the postpartum period pose substantial risks to women and can result in significant maternal morbidity and mortality. However, there is much less attention on postpartum care compared to pregnancy and childbirth. The goal of this study was to gather information on women’s knowledge of postpartum care and complications, recovery practices after childbirth, perceived barriers to receiving care during the postpartum period, and educational needs in four health centers. The findings can inform the development of appropriate curriculum and interventions for postnatal care education in similar settings. Methods A descriptive qualitative study design was employed. Eight focus group discussions were conducted among 54 postpartum women who delivered in four health centers in Sagnarigu District in Tamale, Ghana. Audio recordings of focus group data were transcribed and translated, and thematic analysis was conducted. Results There were six main themes that emerged from the focus group discussions: 1) baby focused postpartum care; 2) postpartum practices; 3) inadequate knowledge ofpostpartum danger signs; 4) barriers to accessing postpartum care 5) experiences of poor mental health; and 6) need for postpartum education. Conclusions Postpartum care for women in this study was primarily perceived as care of the baby post-delivery and missing key information on physical and mental health care for the mother. This can result in poor adjustment postpartum and critically, a lack of knowledge on danger signs for common causes of morbidity and mortality in the postpartum period. Future research needs to understand how to communicate important information on postpartum mental and physical health to better protect mothers in the region.